2017
DOI: 10.4236/ojcm.2017.71003
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Open-Holed CFRP Laminates with Initially Cut Fibers

Abstract: Carbon fiber-reinforced plastic (CFRP) laminates with initially cut fibers (ICFs) have good formability without large degradation of static strength; however, their fatigue behavior has not been investigated thus far. In this paper, we investigated fatigue behavior and damage progress of open-holed CFRP laminates with ICFs having interlayers. Three types of CFRP laminates were employed: a laminate without ICF fabricated using an autoclave (Continuous-A), a laminate with ICF fabricated using an autoclave (ICF-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…As complex structures are often required in the industry, new composite manufacturing routes have to be developed and properties have to be examined. Sudarsono et al [172] investigated the influence of open holes on the fatigue performance of quasi isotropic ICF CFRP manufactured in autoclave (ICF-A) and through press moulding (ICF-P), and compared against standard CFRP (continuous fibre). They reported that the fatigue strength of ICF-P was about 20% that of the ICF-A, and was slightly higher than that of the continuous CFRP.…”
Section: Effect Of Open Holes and Notches On The Fatigue Properties Omentioning
confidence: 99%
“…As complex structures are often required in the industry, new composite manufacturing routes have to be developed and properties have to be examined. Sudarsono et al [172] investigated the influence of open holes on the fatigue performance of quasi isotropic ICF CFRP manufactured in autoclave (ICF-A) and through press moulding (ICF-P), and compared against standard CFRP (continuous fibre). They reported that the fatigue strength of ICF-P was about 20% that of the ICF-A, and was slightly higher than that of the continuous CFRP.…”
Section: Effect Of Open Holes and Notches On The Fatigue Properties Omentioning
confidence: 99%
“…Therefore, intensive study on the fatigue behavior of notched FRP laminates is [ 1 , 2 , 3 , 4 ] required. Many researchers have studied the effect of holes within FRP composites [ 5 , 6 ] but only a few with regard to the layup arrangement and its effects on the strength of the material.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [ 1 , 2 , 4 , 5 , 6 , 7 , 8 ], many authors identified experimentally and numerically there is a high stress concentration around the edge of a hole. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…6, No. 4;2017 Figure 2 shows the BZT-PFE1010-PX milling machine. With the help of two clamps, sample was tensioned on the work table and a perpendicular load was applied using a drill tool.…”
Section: Input Variables Variationmentioning
confidence: 99%
“…6, No. 4;2017 Measured matrix damage lengths of the individual samples were plotted over the different carbon fiber layers as shown in Figure 14. It becomes clear that at constant power of 750 W, matrix damage length for each layer decreases with increase in feed speed.…”
Section: Co 2 Laser Machinementioning
confidence: 99%